2017
DOI: 10.1097/md.0000000000007411
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nonsteroidal aromatase inhibitors on steroid profile in a Chinese population

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…For that reason, proposed as good markers were the ratios A/Σ estrogens and Et/Σ estrogens. A study of 41 female and male Chinese subjects was performed by administering aminoglutetimide, anastrazol and letrozol, and it was also concluded that there was no common trend among the ABP biomarkers and the best markers were those related to estrogens …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For that reason, proposed as good markers were the ratios A/Σ estrogens and Et/Σ estrogens. A study of 41 female and male Chinese subjects was performed by administering aminoglutetimide, anastrazol and letrozol, and it was also concluded that there was no common trend among the ABP biomarkers and the best markers were those related to estrogens …”
Section: Resultsmentioning
confidence: 99%
“…19 A study of 41 female and male Chinese subjects was performed by administering aminoglutetimide, anastrazol and letrozol, and it was also concluded that there was no common trend among the ABP biomarkers and the best markers were those related to estrogens. 20 The variations of the parameters of the steroid module of the ABP did not exceed 30% except for 5βAdiol for volunteer 1. It is worth mentioning that the time of collection was for more than two circadian cycles, so these variations obviously are influenced by physiological fluctuation.…”
Section: Endogenous Steroid Profilementioning
confidence: 87%
See 1 more Smart Citation
“…8 However, if, despite the lack of evidence, it is deemed to be true that letrozole is capable of somehow increasing testosterone and/or androstenedione levels in premenopausal female athletes, when they use this AI, then their serum steroid profiles would become somehow altered or disrupted. 38,39 In particular, their androgen levels should increase with respect to the normal range and their estrogens should be suppressed. If this is not true, then there is no reliable evidence to suggest that letrozole is capable of having a doping effect.…”
Section: Letrozole As a Performance-enhancing Substance In Womenmentioning
confidence: 99%
“…The assay's LODs ranged from 0.1 ng/mL to 20 ng/mL, demonstrating the methods ability to quantifying a total of 22 urinary steroids. The utility of a steroid profile that includes estrogens (in addition to the commonly monitored androgens) to indicate the misuse of non‐steroidal aromatase inhibitors was assessed by Xing et al While aromatase inhibitors such as aminoglutethimide, letrozole, and anastrozole are efficiently analyzed by routine targeted LC–MS(/MS) methods, complementary information derived from the steroid profile may assist in detecting their misuse. In a study including 20 male and 21 female volunteers, either aminoglutethimide (2 × 250 mg/day, 3 days), letrozole (2.5 mg/day, 5 days), or anastrozole (1 mg/day, 5 days) were administered orally.…”
Section: Anabolic Agentsmentioning
confidence: 99%